2004
DOI: 10.1038/sj.onc.1207455
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 is required for glioma development in a mouse model

Abstract: The pleiotropic cytokine interleukin-6 (IL-6) contributes to malignant progression and apoptosis resistance of various cancer types. Although IL-6 is elevated in malignant gliomas, and glioma cells respond to IL-6, its functional role in gliomagenesis is unclear. We have investigated this role of IL-6 in a mouse model of spontaneous astrocytoma by crossbreeding glial fibrillary acidic protein (GFAP)-viral src oncogene transgenic mice with IL-6-deficient mice. We show here that ablation of IL-6 prevents tumour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
134
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(140 citation statements)
references
References 41 publications
(50 reference statements)
4
134
0
2
Order By: Relevance
“…Recent studies have shown that STAT3 is constitutively activated in the vast majority of malignant glioma tissues and cell lines (Rahaman et al, 2002;Schaefer et al, 2002;Weissenberger et al, 2004). However, there is controversy regarding which cell types in tumor tissues express activated STAT3: tumor cells or tumor endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that STAT3 is constitutively activated in the vast majority of malignant glioma tissues and cell lines (Rahaman et al, 2002;Schaefer et al, 2002;Weissenberger et al, 2004). However, there is controversy regarding which cell types in tumor tissues express activated STAT3: tumor cells or tumor endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main molecular signatures of malignant glioma is dysregulation of the EGFR pathway manifesting as amplification and mutation of EGFR and mutation of phosphatase and tensin homologue deleted on chromosome ten (PTEN) (Kapoor and O'Rourke, 2003;Kondo et al, 2004). Another line of evidence has shown that interleukin 6 (IL-6) expression or STAT3 activation is often detected in malignant glioma tissues, whereas neither feature is detected in normal brain tissue (Van Meir et al, 1990;Lichtor and Libermann, 1994;Rahaman et al, 2002;Schaefer et al, 2002;Weissenberger et al, 2004). Taken together, these findings suggest that STAT3 is activated through EGFR dysregulation and the aberrant expression of IL-6 in malignant glioma cells and that the inhibition of STAT3 may be a new tumor-selective strategy for malignant glioma.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of these two interleukins are correlated with the degree of malignancy in gliomas (Huettner et al, 1995;Sasaki et al, 2001) as well as increased proliferation and migration of glioma cell lines (Huettner et al, 1997;Wang et al, 2009). In particular, interleukin-6 ablation prevents tumor formation in a v-src-induced model of gliomagenesis (Weissenberger et al, 2004).…”
Section: Stromal Determinants Of Glioma Formation and Growthmentioning
confidence: 99%
“…10 Finally, by abrogation of IL-6 gene expression in glial fibrillary acidic protein (GFAP)-viral src kinase (v-src) transgenic mice that phenocopy the neuropathology of human astrocytomas, 11 we have recently shown that IL-6 is crucial for glioma development. 12 IL-6 is a member of the neuropoietic cytokine family, which also includes, among others, ciliary neurotrophic factor (CNTF) and leukemia inhibitory factor (LIF). IL-6 not only promotes the survival of certain neuronal cell populations 13 but also the reactive transformation of astrocytes.…”
mentioning
confidence: 99%